O silêncio de Maria: percepção mística sobre a vida de Maria - Cunha, Anna Carolina Bernardi da (2025)
This research reflects on Mary's silence, seeking to address the mystical perception of Marian spirituality. When we think that there has never been a society with so much lack of silence, with so much visual and noise pollution, without knowing how to wait, we realize that silence seems almost like an impossible mission and is actually discouraging. In view of this, we can understand that, when we enter the universe of silence, we realize its relevance and need. It is noted that human beings find themselves increasingly lonely and without time to hear the voice of God within their hearts. In light of this, we ask: What does Mary teach us with her silence? Why was it that among so many women she was the chosen one? The present investigation, limited to the methodology of bibliographical research, therefore aims to reflect on the importance of learning from Mary, so that we are able to provide answers arising from divine intuitions for the world today. The expected results consist of the hope of contributing to a mystical look at modern times